Prosthetic Joint Infection due to Histoplasma capsulatum in a Patient from Trinidad: Workup, Pathology, and Treatment - James Satalich; Julie Reznicek; Alexandra Bryson; Prayag Pershad; Nicholas Hooper; Jibanananda Satpathy (Case Reports in Orthopedics)
Histoplasma capsulatum is a rarely reported cause of prosthetic joint infections. This current case report is of a patient from Trinidad, with a history of a right total knee replacement (TKR), who underwent a successful two-stage revision due to a Histoplasmosis capsulatum periprosthetic joint infection (PJI). This case report offers a unique treatment plan to successfully treat Histoplasmosis capsulatum periprosthetic joint infections and emphasizes the importance of obtaining an accurate travel history.